PENERAPAN ASAS ULTIMUM REMEDIUM DALAM PENEGAKAN HUKUM PIDANA LINGKUNGAN HIDUP - Imam Budi Santoso; Taun Taun (University Of Bengkulu Law Journal, 2018)
The enforcement of environmental law in Indonesia today is growing , environmental laws and regulations are continuously equipped for sustainable development. But, enforcement of environmental law is still not as expected, in environmental law enforcement there are several ways of settlement that must be taken, administratively, alternatives dispute resolution and criminal law, but in criminal law enforcement regulated in Article 100 paragraph (2) of Law Number 32 Year 2009 on Environmental Protection and Management, criminal acts can only be applied if the administrative sanction is not complied with or violation is more than one time, then in explanation point 6 of Law Number 32 Year 2009 on Environmental Protection and Management, enforcement of environmental criminal law should pay attention to the principle of ultimum remedium which requires the application of criminal law enforcement as a last resort after the implementation of administrative law enforcement is deemed unsuccessful, and the application of the ultimum remedium principle applies only to certain offensive crimes, namely the prosecution of violations of waste water quality standards, emissions, and disturbances. However, if it is related to the legality principle contained in Article 1 paragraph (1) of the Criminal Code and the basis of criminal abrogation, the ultimum remedium principle is contradictory, criminal law should continue based on the principle of legality and stopped by the ultimum remedium principle on the basis of criminal sanction, whereas the basis of criminal abrogation has been clearly defined in the Criminal Code.